2015
DOI: 10.1021/acs.chemrestox.5b00302
|View full text |Cite
|
Sign up to set email alerts
|

Guanine Oxidation Product 5-Carboxamido-5-formamido-2-iminohydantoin Induces Mutations When Bypassed by DNA Polymerases and Is a Substrate for Base Excision Repair

Abstract: Guanine (G) is a target for oxidation by reactive oxygen species in DNA, RNA and the nucleotide pool. Damage to DNA yields products with alternative properties toward DNA processing enzymes compared to the parent nucleotide. A new lesion, 5-carboxamido-5-formamido-2-iminohydantoin (2Ih) bearing a stereocenter in the base, was recently identified from the oxidation of G. DNA polymerase and base excision repair processing of this new lesion has now been evaluated. Single nucleotide insertion opposite (S)-2Ih and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 83 publications
1
23
0
Order By: Relevance
“…Because the action of APE1 on an AP results in increased transcription, the present experiments address how oxidations yielding APs, such as LSD1-generated H 2 O 2 followed by Fenton chemistry, can change the transcriptional output of a gene without requiring OG. However, other G oxidation products from Fenton chemistry, such as the hydantoin products (24,25), are substrates for the NEIL1 and 2 glycosylases and do not require APE1 (28,29) and, therefore, would not impact transcription via the mechanism outlined unless additional factors are involved. Thus, further questions remain concerning how an indiscriminate oxidant like H 2 O 2 liberated by LSD1 or LSD2 would have evolved to write OG at critical locations for gene induction.…”
Section: Significancementioning
confidence: 99%
“…Because the action of APE1 on an AP results in increased transcription, the present experiments address how oxidations yielding APs, such as LSD1-generated H 2 O 2 followed by Fenton chemistry, can change the transcriptional output of a gene without requiring OG. However, other G oxidation products from Fenton chemistry, such as the hydantoin products (24,25), are substrates for the NEIL1 and 2 glycosylases and do not require APE1 (28,29) and, therefore, would not impact transcription via the mechanism outlined unless additional factors are involved. Thus, further questions remain concerning how an indiscriminate oxidant like H 2 O 2 liberated by LSD1 or LSD2 would have evolved to write OG at critical locations for gene induction.…”
Section: Significancementioning
confidence: 99%
“…Because OG is always observed in higher concentrations, it is regarded as a good indicator for monitoring cellular oxidative stress. In light of recent in vitro oxidations of G to yield 2Ih in greater levels than OG [62, 154], 2Ih may exist in cells at high levels; however, in cellulo studies to detect 2Ih have yet to be reported…”
Section: Products Of G Oxidation Are Mutagenic On the Basis Of Celmentioning
confidence: 99%
“…When 2Ih is in the template strand, dATP or dGTP are inserted opposite the lesion by a polymerase in vitro with a preference for dGTP [154]. Verification of 2Ih causing mutations in cellulo by the REAP assay consistent with the in vitro studies has yet to be conducted.…”
Section: Products Of G Oxidation Are Mutagenic On the Basis Of Celmentioning
confidence: 99%
See 2 more Smart Citations